Self-devouring growth : a planetary parable as told from Southern Africa - Livingston, Julie (Critical global health., 2019)
"Under capitalism, economic growth is seen as the key to collective wellbeing. In Self-Devouring Growth Julie Livingston upends this notion, showing that while consumption-driven growth may seem to benefit a particular locale, it produces a number of unacknowledged, negative consequences that ripple throughout the wider world. Structuring the book as a parable in which the example of Botswana has lessons for the rest of the globe, Livingston shows how fundamental needs for water, food, and transportation become harnessed to what she calls self-devouring growth: an unchecked and unsustainable global pursuit of economic growth that threatens catastrophic environmental destruction. As Livingston notes, improved technology alone cannot stave off such destruction; what is required is a greater accounting of the web of relationships between humans, nonhuman beings, plants, and minerals that growth entails. Livingston contends that by failing to understand these relationships and the consequences of self-devouring growth we may be unknowingly consuming our future"--